Perancangan User Experience Aplikasi Mobile Peserta Event Berbasis Sistem Dengan Menggunakan Metode Design Thinking (Studi Kasus : Dilo Malang) - Risma Putri Auliasari; Herman Tolle; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In 2017, the APJII survey results recorded an increase in internet users in Indonesia from 132.7 million people in 2016 to 143.26 million people in 2017. With the development of technology, this also resulted in the growth of startups in Indonesia growing. According to Indonesia's Tech Startup Report 2018, startup companies in Indonesia are becoming more attractive and have a big influence on society. This is what led Digital Innovation Lounge (Dilo) to open a branch in Malang. Dilo is a startup that provides seminar events on current technological developments. The event held by DILo Malang has a special interest in the community. However, with the event, more and more DILo experienced difficulties when making monthly reports from pre-event to post-event regarding the number of participants. In addition, the system for renting a meeting room or lounge is still conventional. Through these problems the authors offer a solution to DILo Malang in the form of a User Experience Design for the Event participant mobile application based on a system with the results of a prototype using the Design Thinking method. The results of testing the mobile application design of the event participants showed the results of testing the efficiency aspects with a value of 95.95%, the results of testing the effectiveness aspects of 97.77% and the results of testing aspects of user satisfaction with the SUS questionnaire got a value of 98.5. The results of the tests carried out get a value above average so that the testing of the mobile application design for the participants of this event shows positive results.